KINERJA KEUANGAN PADA PT. SERMANI STEEL MAKASSAR BERDASARKAN RETURN ON INVESTMENT DAN TOTAL ASSET TURNOVER - Idham Mannaga (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
This study aims to determine the company's financial performance through analysis of Return On Investment and Total Asset Turnover, to determine the level of corporate investment in fixed assets during the operation of the company running the company, to megetahui magnitude of the effect of financial performance based on Return On Investment and Total Asset Turnover to changes in asset investment remain on the company. The method of analysis used in this study is quantitative analysis: Analysis of financial ratios that are Quantitative Analysis of Return On Investment, Total Asset Turnover analysis and Analysis of Fixed Asset Investment. These results indicate that: the company's overall performance is good enough, it can be demonstrated through the company's ROI fluctuated from year to year. This happens because the company is unable to maintain and even increase its net profit, ROI, companies do not have the strong influence of the fixed asset investment decisions, and partly influenced by costs such as interest income, sales, fund operating expenses, Total Asset Turnover a company fluctuates year after a tender, where the Total Asset Turnover was highest in 2007 and terndah occurred in 2009 and 2010. Things that cause the Total Asset Turnover is low even at its lowest level in 2009, particularly due to high inventories and the sale had occurred and the company's fixed assets investment increased from year to year, this was due to the purchase of fixed assets of the company.